Digitalisasi Sekolah Sungai Code dalam Upaya Optimalisasi Edukasi Lingkungan dan Mitigasi Bencana - Ramadhiana, Hasna Zalfa; Soliana, Afra Putri; Dalimunte, Zainal Arrasyid; Hariadi, Nadia Dwi Aprilla Putri; Cahyani, Cantika Putri; Sukoco, Heru (Puslitbang Sekawan Institute Nusa Tenggara, 2025)
The DigiCODE program implemented as part of PKM 2025, is a initiative for the digitalization of environmental education and disaster mitigation media at Yogyakarta Code River School. This program is a solutions to the limitations of the Code River School’s educational activities, which have been conventional and not documented in a sustainable manner, as well as the dependence of its activities on facilitators. The low utilization of technology is a challenge for the Code River community in maintaining the sustainability of environmental education in the riverbank area. This community service activity aims to increase the capacity of the community in managing sustainable digital-based educational media while strengthening public awarness of environmental conservation and disaster mitigation. The Participatory Rural Appraisal (PRA) method which emphasizes active community participation, was applied in this activity. The DigiCODE program was implemented in four subprograms: CODEBook, CODEQuick, CODEHistory, and CODELive, which focus on digital media development, historical documentation, and digital literacy training. The results of the activity showed an 88.75% increase in partner’s digitalization capabilities and an 87.5% increase in participant’s understanding of environmental and disaster mitigation. This program produced pocket book, QR code-based educational boards, a mini gallery, social media and a website. In addition, young cadres were formed as community administrators to maintain the program’s sustainability. Overall, DigiCODE contributes to strengthening an independent, participatory, and sustainable system of environmental and disaster education based on digital technology.